Panax ginseng metabolite (GIM-1) modulates the effects of monobutyl phthalate (MBP) on the GPR30/GPER1 canonical pathway in human Sertoli cells - de Freitas, André Teves A.G. [UNESP]; Pinho, Cristiane Figueiredo [UNESP]; Aquino, Ariana Musa [UNESP]; Domeniconi, Raquel Fantin [UNESP]; Justulin, Luis Antonio [UNESP]; Scarano, Wellerson Rodrigo [UNESP] (Elsevier, 2020)
This study was performed to evaluate the effect of monobutyl phthalate (MBP) on GPR30-activated pathways in Sertoli cells. Additionally, we tested if GIM-1 (Panax ginseng metabolite) modulates MBP action. Human Sertoli cells (HSeC lineage) were exposed to MBP and/or GIM-1 for 30 min, 1, 12, and 48 h. Four experimental treatments were performed: control (DEMEM/F12 medium), MBP, GIM-1, and MBP + GIM-1. The results indicate that MBP activates GPR30, PKA, Src, EGFR, and the ERK1/2 proteins, while GIM-1 inhibits PKA, Src, ERK1/2, and the AKT pathway. MBP also enhances Cofilin expression, decreasing F-actin intensity on the cell surface in a short time. The combined exposure demonstrated a functional antagonism between compounds. Collectively, these data show that MBP activates GPR30 in Sertoli cells, and GIM-1 modulates this response, playing a protective role in Sertoli cells exposed to MBP.
Keywords: GIM-1; GPR30/GPER1; MBP; Panax ginseng; Sertoli cells